2021
DOI: 10.1177/11297298211023295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurolidine citrate and unfractionated heparin on inflammatory state and dialysis adequacy in hemodialysis patients

Abstract: Background and aim: HD patients using dialysis catheters have been associated with chronic inflammatory state. In Egypt 6.6% of HD patients use catheters, of which short term catheters represent 59.6% and 40.4% with long-term catheters. In this study, we aimed to assess the effect of Taurolidine citrate and unfractionated heparin combination (Taurolock-hep500™) as a lock solution compared to unfractionated heparin alone on inflammatory markers, incidence of catheter related blood stream infections (CRBSI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Ezzat et al reported that the use of taurolidine for temporary hemodialysis catheters was associated with lower inflammation markers, lower incidence of catheter-related bloodstream infections, and better catheter performance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ezzat et al reported that the use of taurolidine for temporary hemodialysis catheters was associated with lower inflammation markers, lower incidence of catheter-related bloodstream infections, and better catheter performance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has suggested that UFH can alleviate sepsis-induced ALI by reducing the levels of IL-6 in bronchoalveolar lavage fluid and improving the tight junctions in human lung microvascular endothelium by inhibiting the ERK1/2 MAPK pathway and downregulating the expression of claudin 5, occluding and ZO-1 (Liu et al, 2019). Furthermore, the use of UFH as a lock solution in catheters in patients undergoing hemodialysis also reduces the levels of IL-6 (Ezzat et al, 2021). Extracellular histones are known to be major contributors to organ dysfunction and death in patients with sepsis as they cause problems in the microcirculation.…”
Section: B Trauma and Lung Injurymentioning
confidence: 99%